EVALUATION OF NGABEAN SECONDARY CANAL IRRIGATION NETWORK, NGAWI DISTRICT PART OF SALURAN INDUK MADIUN IRRIGATION AREA - Nusantara, Danayanti Azmi Dewi; Hartiningsih, Poppy Fajar Putri (Fakultas Teknik Universitas Tanjungpura, 2024)
The SIM Irrigation Area has an area of 10,860 Ha and a primary canal length of 27,022 m, which passes through the Regencies of Madiun, Magetan, Ngawi, and Madiun City. One of the secondary canals in the D.I SIM is the Ngabean Secondary Canal, located in Ngawi Regency. This canal receives the main water supply from Jati Dam, 25% of the primary dam discharge and water withdrawal from the Ngabean Dam intake of 0.45 m3/ha. However, this value only meets the water needs of some of the irrigation areas. Due to the limited supply from the Jati Bendung, the government is working on rehabilitation work at the Jati Bendung. Apart from that, the Ngabean Secondary Canal also experienced a reduction in the irrigation area from 1840 ha to 1818 ha, to be precise in the NG3 Ki tertiary plot, which had an initial area of 120 ha to 98 ha. Therefore, an evaluation of the Ngabean Secondary Canal is needed to determine the value of water demand, water availability before and after rehabilitation and land reduction, and increasing agricultural profits.From the results of the analysis that has been carried out, it was concluded that the highest dependent flow at Ngabean Dam was 5.00 m3/s, and the lowest was 0.01 m3/s. Meanwhile, in conditions before rehabilitation, the highest dependent flow of Jati Dam was 1.01 m3/s, and the lowest was 0.00 m3/s with water withdrawal at the intake of 25%, able to fulfill the planting pattern of paddy (15%)-crops (75%)-crops (50%) generated a production profit of IDR 8.794.123.880,00. Meanwhile, after rehabilitation, the highest was 5.93 m3/s, and the lowest was 3.21 m3/s with an intake of 32%, able to fulfill the planting pattern of paddy (100%)-paddy (100%)-paddy (100%), resulting in a production profit of IDR 83, 564,115,480.00 with the highest irrigation water requirement value of 3.10 m3/sec. Apart from that, the existing canal dimensions still meet the requirements after land reduction, so no changes to the canal dimensions are required.